Construction of experimentally validated lncRNA-miRNA‐mRNA Regulatory Network in Keratoconus - Mahmanzar, Mohammadamin; Maghsoudloo, Mazaher; Adhami Moghadam, Farhad; Shojaei, Ahmad (Journal of Ophthalmic and Optometric Sciences, 2020)
Objectives: Keratoconus is a rare genetic eye disease that affects the cornea. It can be passed down from parents to children. Scientists are working on finding the mechanism of development and pathology of this disease. So, identifying gene expression patterns and the regulator factors that impact mRNA expression level could modulate Keratoconus pathogenesis. As these regulatory factors, Long non-coding RNAs (LncRNAs) in competition with mRNA can interact with microRNAs (miRNAs), regulating gene expression. However, the roles of competitive endogenous RNA (ceRNA) networks consisting of lncRNAs, miRNAs, and messenger RNAs (mRNAs) remain Keratoconus unclear. This study was performed to explore novel regulatory networks in Keratoconus disorder. Methods: The mRNA expression profiles were retrieved from the Gene Expression Omnibus (GEO). Candidates differentially expressed genes (DEGs) were identified to investigate miRNA and mRNA, respectively and construct a lncRNA-miRNA-mRNA network through a comprehensive bioinformatics strategy and analysis. Results: Through analyzing GSE112155 datasets, 1lncRNA, XIST, was identified. 488 miRNAs and twenty-nine mRNA were obtained as XIST targets from databases that deposit experimental data. So, lncRNA-miRNA- mRNA regulatory network was constructed based on the interactions. Through centralities analysis of the network, top 10 hub nodes (CDKN1A, XIAP, MAPK1, XIST, SP1, AR, LARP1, MACC1, PTEN, EGFR) were discovered. Our data showed that among miRNAs, has-mir-2110 plays key interaction role in this network. Moreover, by preformed pathway analysis, TGF-beta Signaling Pathway was identified. Conclusions: Our study provides a novel perspective on the regulatory mechanism of Keratoconus involving Competing for endogenous RNA (ceRNA), including lncRNA, miRNAs, and mRNA.